A multiscale topological design method of geometrically asymmetric porous sandwich structures for minimizing dynamic compliance. (February 2022) - Zhang, Yan; Zhang, Lei; Ding, Zhe; Gao, Liang; Xiao, Mi; Liao, Wei-Hsin
Graphical abstract: Highlights: A design method is proposed for geometrically asymmetric porous sandwich structure. The multiscale topological design method is to minimize dynamic compliance. Face-sheet thickness and porous core configuration are simultaneously optimized. Variable thickness sheet method and parametric level set method are adopted. Several 2D and 3D numerical examples are investigated and compared. Abstract: Compared with conventional sandwich structures with two identical face sheets, geometrically asymmetric porous sandwich structures (GAPSSs) can achieve better dynamic performances under certain load and boundary condition, since they provide more choices for geometric design. However, current studies regarding the GAPSSs are mainly analytical- and experimental-based methods with predefined face sheet thicknesses and core configurations, few works investigate the GAPSSs by optimization method. This paper presents a multiscale topology optimization method of the GAPSSs, which is capable of designing both thicknesses of two solid face sheets at macroscale and configurations of porous core at microscale for minimizing dynamic compliance. Specifically, at macroscale, a variable thickness sheet method is employed to optimize the thicknesses of two solid face sheets. Then, at microscale, a parametric level-set method integrated with a numerical homogenization approach is applied to topologically optimize the configuration of the periodic unit cell. The method of moving asymptotes is adopted to update the design variables at both scales. Several 2D and 3D numerical examples are illustrated to show the effectiveness and advantages of the proposed method for designing the GAPSSs. The results indicate that the dynamic compliance of the optimized GAPSSs show superior advantages over the conventional sandwich structures with identical face sheet thicknesses and predefined lattice core.